Time dependent second grade fluid between two vertical oscillating plates with heat transfer effect - Muhammad Ismail, Mohmand; Mustafa, Mamat; Qayyum, Shah (2017)
In this paper, the flow of unsteady second grade fluid problem is examined between two vertical and oscillating plates. The parallel plates are oscillating. The heat transfer effect is taken on the plates. Optimal Homotopy Asymptotic Method (OHAM) is used for solution. Analytical solution is obtained. Effect of several physical parameters are studied as well as discussed in details.